402. Breakthrough Pneumocystis jirovecii Pneumonia Among Cancer Patients: Opportunity for Antimicrobial Stewardship?. (26th November 2018) - Roncaioli, Steven; Bryan, Andrew; Stohs, Erica; Liu, Catherine; Sweet, Ania; Pergam, Steven
Abstract: Background: Despite available prophylaxis, Pneumocystis jirovecii pneumonia (PJP) still occurs in immunocompromised hosts. We set out to determine the overall burden of PJP among cancer patients in the modern era at our cancer center. Furthermore, we sought to describe reasons for failure to use prophylaxis among these patients. Methods: In this retrospective cohort study, we identified PJP cases among patients admitted between January 2007 and December 2016 at our center. PJP was defined as any positive test (immunofluorescence or PCR) from sputum and/or bronchoalveolar lavage. Patient demographics, underlying malignancy, anti-pneumocystis antibiotics and mortality were assessed through electronic medical records. Current National Comprehensive Cancer Network (NCCN) guidelines were used to determine who should have received prophylaxis. Cases not on prophylaxis at the time of diagnosis were reviewed to determine reasons why prophylaxis was not administered. Incidence of PJP for the last 5 years of the study was estimated based on a Poisson distribution. Results: A total of 37 patients had confirmed PJP over the 10-year study period. The majority were male (68%) with a median age of 60 years (IQR: 47, 67). The most common underlying malignancy was acute myeloid leukemia (24%); 24/37 (65%) were bone marrow transplant recipients. The 5-year incidence between 2012 and 2016 was 2.28 per 10, 000 inpatient days (95% CI, 1.50–3.32). There was no evidence of clustering of PJP diagnoses. Overall, 26/37 (70%) of PJP patients were not on prophylaxis at the time of diagnosis, 12 of whom met NCCN criteria for use. Twenty-three were deceased by the end of the study with 11/23 (48%) deaths occurring within 30 days of diagnosis. The main reason prophylaxis was not administered was neutropenia (19%). A documented sulfa allergy was noted in seven PJP cases (19%); 2/7 (29%) were not administered alternate prophylaxis despite recommendations for use. Conclusion: PJP incidence in this large cohort of cancer patients was low, but one-third of patients who developed PJP were not on recommended prophylaxis in accordance with NCCN guidelines. Infection Prevention and Antimicrobial Stewardship teams should enhance efforts to address missed opportunities for PJP prophylaxis in high-risk patients. Disclosures: S. Pergam, Merck: Consultant, Consulting fee. Chimerix: Consultant, Consulting fee.